2020
DOI: 10.1038/s41523-020-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic response of ER+/HER2− breast cancers differs according to the molecular Basal or Luminal subtype

Abstract: The genomics-based molecular classifications aim at identifying more homogeneous classes than immunohistochemistry, associated with a more uniform clinical outcome. We conducted an in silico analysis on a meta-dataset including gene expression data from 5342 clinically defined ER+/HER2− breast cancers (BC) and DNA copy number/mutational and proteomic data. We show that the Basal (16%) versus Luminal (74%) subtypes as defined using the 80-gene signature differ in terms of response/vulnerability to systemic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 74 publications
0
33
0
2
Order By: Relevance
“…Among the HR‐positive cases with an overall response of 11%, those reclassified as Basal‐like achieved pCR of 32% 112 . Recently, the analysis of a large in silico meta‐dataset of gene expression results ( n = 5342) reinforced previous results reporting chemotherapy response rates of 32% (27/85) for Basal‐like and 9% (42/452) for the Luminal subtype among HR+ patients 145 . Interestingly, expression profiles positioned reclassified HR+/Basal‐like group between the HR‐positive/Luminal and HR‐negative/Basal‐like subtype, suggesting that a different cell‐of‐origin should be considered for this group.…”
Section: Clinical Implications Of Classification Discordancementioning
confidence: 70%
See 1 more Smart Citation
“…Among the HR‐positive cases with an overall response of 11%, those reclassified as Basal‐like achieved pCR of 32% 112 . Recently, the analysis of a large in silico meta‐dataset of gene expression results ( n = 5342) reinforced previous results reporting chemotherapy response rates of 32% (27/85) for Basal‐like and 9% (42/452) for the Luminal subtype among HR+ patients 145 . Interestingly, expression profiles positioned reclassified HR+/Basal‐like group between the HR‐positive/Luminal and HR‐negative/Basal‐like subtype, suggesting that a different cell‐of‐origin should be considered for this group.…”
Section: Clinical Implications Of Classification Discordancementioning
confidence: 70%
“…Supportive of this is a finding that most genes associated with endocrine sensitivity were also found associated with chemotherapy resistance 148 . Conversely, in these retrospective studies, non‐Luminal subtypes present within HR‐positive disease showed lesser benefit from adjuvant hormone therapy, suggesting estrogen‐independency of these tumors 137,145,148 . The activation of EGFR has been recently identified as a resistance mechanism to endocrine therapy and may be responsible for poorer endocrine therapy responsiveness of HER2‐Enriched portion of HR‐positive patients 149 .…”
Section: Clinical Implications Of Classification Discordancementioning
confidence: 89%
“…Molecular signatures based on gene expression pattern include hormonal receptors such as androgen receptor (AR), estrogen receptor (ER), human epidermal growth factor receptor 2 (HER2) and progesterone receptor (PR). Molecular subtypes can predict baseline prognosis, distant relapse-free survival and therapeutic decision-making strategies [6][7][8][9][10][11][12][13][14]. Docetaxel (DOCE) is a taxane derivate used in BC and PC.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a heterogeneous disease that has multiple molecular and morphological subtypes. 1 The most common morphological type is invasive breast carcinoma of no special type (IBC NST), whose molecular subtypes are characterized by three main phenotypes: luminal (estrogen receptor– and/or progesterone receptor–positive), HER2-overexpressing, and triple-negative. 2 The molecular subtype is associated with the metastatic potential of breast cancer cells: the luminal tumor subtypes have a lower malignant progression rate and a better response to pharmacotherapy compared to those of the HER2-overexpressing subtype and triple-negative subtype of breast cancer.…”
Section: Introductionmentioning
confidence: 99%